“Guardiãs da trilha dourada”: o movimento de mulheres das ilhas de Belém (MMIB) e as práticas coletivas no enfrentamento à violência doméstica e familiar contra as mulheres ribeirinhas na ilha de Cotijuba-PA - MARÇAL, Ana Léa Chagas (Universidade Federal do Pará, 2023)
The present research portrays the history of the "Guardians of the Golden Trail", the Women's Movement of the Islands of Belém (MMIB) that operates in the Island of Cotijuba (PA), reflecting on the collective practices in the face of violence against women experienced in the particular Amazonian riverside. Divided into three "scenes", alluding to the filmic narrative, the research addresses in the first scene how the socio-spatial dynamics of exclusion and the non-recognition of the identity and way of life of the riverside communities of Belenenses have given rise to serious and complex social and economic problems that affect the inhabitants of the region, among them, the precariousness of basic services and the absence of public policies aimed at the local population, exacerbated by the urban-centric vision that favored the expansion of the metropolis to the detriment of this inseparable environment of its territory. In this context, the research proposes to highlight the silencing and vulnerability of Amazonian riverside women, positioned on the margins of official history – and academic debate – with the practices of resistance as the central point of collective female identities, presenting the true protagonists of this history. In the second scene, the trajectory of the struggle of feminist and women's movements for the recognition of rights and the legislative achievements of protection and combat against domestic and family violence against women is shown, highlighting the creation of the Maria da Penha Law and the implementation of the service network for women in situations of violence in the State of Pará. In the third scene, the emergence of emancipatory collective actions coordinated by women is highlighted, as a counter-movement capable of generating social transformations, showing the pioneering action of the Women's Movement of the Islands of Belém (MMIB) in confronting domestic and family violence against riverside women in the insular region of the municipality of Belém (PA), specifically on the island of Cotijuba. In the methodological river course, a bibliographic review was used, in addition to field research of ethnographic inspiration through participant observation and narrative interviews with the interlocutors. As an interventional proposal, a documentary was made that consisted of the scripting and editing of the interviews captured during the field visits with the purpose of producing audiovisual material for sharing and socializing the research with the academic and local community.